Global ecology in human perspective - Southwick, Charles H. (New York : Oxford University Press, 1996)
A textbook covering the study of human ecology and global ecology. Topics covered include ecological principles relevant to global concerns and human impact on the environment The central theme of the book deals with the ways humans are altering the earth and how these changes affect human life
Includes bibliographical references and index.
Keywords: Environmental sciences; Nature -- Effect of human beings on; Pollution